2020
DOI: 10.1111/jdi.13468
|View full text |Cite
|
Sign up to set email alerts
|

Admission hyperglycemia as an independent predictor of long‐term prognosis in acute myocardial infarction patients without diabetes: A retrospective study

Abstract: Aims/Introduction The predictive value of admission hyperglycemia in the long‐term prognosis of acute myocardial infarction patients is still controversial. We aimed to investigate this value based on the diabetes status. Materials and Methods We carried out a multicenter, retrospective study of 1,288 acute myocardial infarction patients enrolled in 11 hospitals between March 2014 and June 2019 in Chengdu, China. The patients were classified into those with diabetes and those without diabetes, each was further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 31 publications
0
23
1
Order By: Relevance
“…Recent literature defined hyperglycemia as serum glucose in the range between >122 mg/dL. [42] up to >198 mg/dL [41], which may result in a diverse distribution of subjects per groups in these studies. Secondly, a lower proportion of patients without known diabetes received insulin during hospitalization compared with diabetics, even with severe hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature defined hyperglycemia as serum glucose in the range between >122 mg/dL. [42] up to >198 mg/dL [41], which may result in a diverse distribution of subjects per groups in these studies. Secondly, a lower proportion of patients without known diabetes received insulin during hospitalization compared with diabetics, even with severe hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the information on glycaemic status can be useful beyond prediction for shortterm prognosis. Admission glucose is an independent predictor of long-term prognosis in non-diabetic AMI patients [42]. Interestingly, glucose variability between visits to clinic is associated with adverse cardiac remodeling after STEMI, suggesting that the clinical value of glucose and its related parameters is significant and should be investigated further [43].…”
Section: Shr and Glucose As Clinical Outcome Predictorsmentioning
confidence: 99%
“…Clinical studies have confirmed that increased blood glucose levels in the infarct area accelerate anaerobic glycolysis, leading to the production of a large number of acidic metabolites, which cause local paralysis and dilation of blood vessels and damage to the vascular endothelium. Elevated blood glucose level will increase the aggregation ability of red blood cells, reduce the blood flow rate, and promote platelet aggregation and adhesion, leading to the formation of thrombus [ 22 ]. The linear regression equation is the use of regression analysis in mathematical statistics to determine the interdependent quantitative relationship between two or more variables, where r is a statistical indicator first designed by Carl Pearson to indicate the amount of linear correlation between the studied variables, and r ≥ 0.8 is regarded as highly correlated [ 23 ].…”
Section: Discussionmentioning
confidence: 99%